Insights of the AD 1755 Lisbon tsunami in the estuary of the Alcabrichel River (Portuguese western coast) - Tudor, M. (2020)
Studies on extreme marine inundations that affected the Portuguese coast refer mainly to the tsunami of AD 1775, considered the most devastating that affected the Portuguese coast. This work is focused on the recognition of a tsunami deposit in Alcabrichel River estuary and presents the analysis of a sediment core CF2. Lithostratigraphic, sedimentological, geochemical, morphoscopic and microtextural analyses revealed a peculiar deposit, a massive layer (10cm), essentially sandy (>90%), interposed between fine sediments and the radiocarbon dating performed under the scope of R&D Project PTDC/CTE-GIX/104035/2008, placing this event in the chronological proximity of the AD 1755 Lisbon tsunami.